2013
DOI: 10.1088/0031-9155/58/13/4513
|View full text |Cite
|
Sign up to set email alerts
|

Phase-transition thresholds and vaporization phenomena for ultrasound phase-change nanoemulsions assessed via high-speed optical microscopy

Abstract: Ultrasonically activated phase-change contrast agents (PCCAs) based on perfluorocarbon droplets have been proposed for a variety of therapeutic and diagnostic clinical applications. When generated at the nanoscale, droplets may be small enough to exit the vascular space and then be induced to vaporize with high spatial and temporal specificity by externally-applied ultrasound. The use of acoustical techniques for optimizing ultrasound parameters for given applications can be a significant challenge for nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 61 publications
14
96
1
1
Order By: Relevance
“…This circulation of the dynamic system has been reported by Sheeran et al [45] and observed with PFP and PFH nanoparticle droplets in water at 25 °C and 37 °C [46].…”
Section: Bubble Growthsupporting
confidence: 82%
See 2 more Smart Citations
“…This circulation of the dynamic system has been reported by Sheeran et al [45] and observed with PFP and PFH nanoparticle droplets in water at 25 °C and 37 °C [46].…”
Section: Bubble Growthsupporting
confidence: 82%
“…The phase shift capability of PFC nanoparticles will decrease with increasing ultrasound frequency and surface tension. Many of these results have been confirmed with experimental observations [34,45,53].…”
Section: Acoustic Droplet Vaporizationsupporting
confidence: 68%
See 1 more Smart Citation
“…To overcome the size/circulation limitations of microbubbles, researchers have begun using phase change contrast agents (PCCAs), which are injected intravenously as liquid nanodroplets, migrate to the target site, and vaporize into gas microbubbles when exposed to a threshold negative pressure using ultrasound [7]. While in the liquid state, PCCAs can persist in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have focused on the conditions necessary for droplet nucleation 322,328,332,344,370,373 and the vaporization process itself 339,365,374 , only limited information is available regarding the acoustic properties of these newly created microbubbles.…”
Section: Introductionmentioning
confidence: 99%